DESIGN AND REALIZATION OF DIRECTIONAL BIQUAD AND OMNIDIRECTIONAL BIQUAD ANTENNAS AS FIRST PERSON VIEW (FPV) RECEIVER ANTENNAS - Sufa, Sufa; Marpaung, Jannus; Yacoub, Redi Ratiandi (Faculty of Engineering, Universitas Tanjungpura, 2023)
UAV is an unmanned aerial vehicle controlled remotely by a pilot or automatically by pre-programmed instructions. UAVs are equipped with First Person View (FPV) technology, which facilitates user monitoring. FPV monitoring can be done using with goggles and a monitor screen. The monitor screens available in the market typically use dipole antennas as their default antennas. However, the drawback of the default monitor screen antenna is its limited range, typically only reaching up to 200-300 meters. This research focuses on the design and implementation of biquad antennas for FPV receivers in UAV systems operating at a frequency of 5.8 GHz. The aim is to create antennas with a larger reception range from the transmitter compared to the default FPV monitor screen antenna. Simulation results from CST Studio show that the directional biquad antenna has a VSWR value of 1.508, a return loss of -13.867 dB, and a gain of 3.416 dBi. On the other hand, the omnidirectional biquad antenna with 4 lobes has a VSWR value of 1.7065, a return loss of -11.666 dB, and a gain of 1.973 dBi. Meanwhile, the omnidirectional biquad antenna with 6 lobes has a VSWR value of 1.226, a return loss of -19.863 dB, and a gain of 1.865 dBi. In practical testing on the FPV monitor screen, all three types of antennas were successfully realized and able to capture real-time images from the UAV transmitter. The maximum distances achieved are 634 meters for the directional biquad antenna, 352 meters for the omnidirectional biquad 4 lobes antenna, and 545 meters for the omnidirectional biquad 6 lobes antenna.